Laryngeal Langerhans Cell Histiocytosis Presenting with Neck Mass in an Adult Woman - Hesam Jahandideh; Yasser Nasoori; Sara Rostami; Mahdi Safdarian (Case Reports in Otolaryngology)
Langerhans cell histiocytosis (LCH) is a very rare condition that commonly affects the head and neck region. There are very few cases of isolated laryngeal involvement by LCH, mostly reported in pediatric patients. Here, we report a case of laryngeal LCH in a 62-year-old woman presenting with a neck mass several weeks ago. The clinical and histopathological findings are reported with a brief discussion about the disease.